Generation and Propagation of M2 Internal Tides Modulated by the Kuroshio Northeast of Taiwan. Issue 4 (23rd April 2019) - Chang, Hang; Xu, Zhenhua; Yin, Baoshu; Hou, Yijun; Liu, Yahao; Li, Delei; Wang, Yang; Cao, Shengshan; Liu, Antony K.
Abstract: The variability and energetics of M2 internal tides during their generation and propagation through the Kuroshio flows northeast of Taiwan are investigated using a high‐resolution numerical model. The corrugated continental slopes, particularly the I‐Lan Ridge and Mien‐Hua Canyon, are first identified as the energetic sources of M2 internal tides. The domain‐integrated M2 barotropic‐to‐baroclinic conversion rate under the Kuroshio influence is ~2.35 GW, ~0.9 GW of which is generated at the I‐Lan Ridge, ~0.93 GW at the Mien‐Hua Canyon, and ~0.52 GW at the north shelf. The M2 internal tide generation is influenced by the horizontally varying, zonally tilting stratification associated with the Kuroshio. In this situation, the conversion rate decreases by ~30% at the I‐Lan Ridge but increases to within ~10% at the Mien‐Hua Canyon and north shelf, in comparison to the simulation initiated with horizontal homogeneous stratification. Internal tides from multiple sources interfere to form a three‐dimensional baroclinic field. The interference by the internal tides from the Mien‐Hua Canyon and north shelf is refracted by the Kuroshio and exhibits a mesoscale gyre pattern, which can explain the frequent occurrence of internal solitary waves. An energetic along‐slope tidal beam (TBKC) from the I‐Lan Ridge radiates southward against the northward Kuroshio flows, causing strong vertical displacement, which favorably compares with recently reported field measurements. The M2 internal tide energy dissipates primarily near the source sites, and the remaining energy radiates outward over limited distances. Complex topographic features and background currents enhance the internal tide dissipation, which induces strong, inhomogeneous diapycnal mixing. Key Points: The M2 internal tide variability and energetics in the Kuroshio northeast of Taiwan are revealed through high‐resolution numerical simulations The I‐Lan Ridge and Mien‐Hua Canyon are first identified as the prominent and energetic sources of the M2 internal tides The M2 internal tide generation and propagation from corrugated slopes (particularly ridge and canyon) are strongly modulated by the Kuroshio